Solid-supported nitrogen acyclic carbene (SNAC) complexes of gold: preparation and catalytic activity - Tšupova, Svetlana; Cadu, Alban; Rudolph, Matthias; Hashmi, A. Stephen K. (Journal of catalysis, 2017)
A readily accessible route to obtain solid-supported nitrogen acyclic carbene (SNAC) complexes of gold was designed using flow chemistry, and an analogous homogeneous gold complex was synthesized for comparison. Both were screened for counter ions in order to perform the Hashmi phenol synthesis. A recyclability study was performed on the SNAC complex, which showed the high stability of this catalyst, with no observed leaching or gold nanoparticle formation. XPS analysis was employed to confirm the presence of gold and its oxidation state.
Gesehen am 28.08.2017